Sistem Informasi Monitoring Stok Barang Berbasis Web Pada Toko SRC Trisni - Nisa, Tita Aisyah Khoirun; Wijiyanto, Wijiyanto; Santosa, Tri Joko (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
SRC Trisni Store's primary issue is the manual stock item recording method, which results in low operating efficiency, a significant risk of recording errors, and challenges in real-time monitoring of incoming and outgoing products data. In order to streamline the inventory management process, this study intends to develop and deploy an online stock monitoring information system. The Waterfall model, which includes the phases of requirements analysis, system design, implementation, testing, and maintenance, is the approach utilized for system development. According to the system development results, functions like controlling officers, suppliers, admin data, shelves, and arriving and exiting items may all operate as intended. The black box approach of testing demonstrates that every feature functions as intended by the user. To sum up, this technology can let SRC Trisni Store run more smoothly and efficiently by increasing the accuracy and efficiency of stock item management.